Eye bank versus surgeon prepared DMEK tissues: influence on adhesion and re-bubbling rate - Romano, Vito; Kazaili, Ahmed; Pagano, Luca; Gadhvi, Kunal Ajit; Titley, Mitchell; Steger, Bernhard; Fernández-Vega-Cueto, Luis; Meana, Alvaro; Merayo-Lloves, Jesus; Diego, Ponzin; Akhtar, Riaz; Levis, Hannah J; et al. (British journal of ophthalmology, 2022)
AimTo investigate the difference in adhesion and rebubbling rate between eye bank and surgeon prepared Descemet membrane endothelial keratoplasty (DMEK) tissues.MethodsLaboratory and clinical retrospective comparative interventional case series. Research corneal tissues were obtained for laboratory investigation. The clinical study involved patients with endothelial dysfunction who underwent DMEK surgery and tamponade with air. Tissues were stripped using a standard DMEK stripping technique (SCUBA) and shipped as prestripped or loaded in a 2.2 intra-ocular lens cartridge with endothelium facing inwards (preloaded) before transporting from the eye bank to the surgeon. For surgeon prepared tissues, all the grafts were stripped in the theatre and transplanted or stripped in the laboratory and tested immediately. Adhesion force and elastic modulus were measured in the centre and mid-periphery in a laboratory ex vivo investigation using atomic force microscopy, while rebubbling rates were recorded in the clinical study.ResultsThere was no difference in endothelial cell viability between surgeon or eye bank prepared tissue. Surgeon-stripped DMEK grafts in the laboratory investigation showed significantly higher elastic modulus and adhesion force compared to prestripped and preloaded tissues (p<0.0001). In the clinical data, rebubbling rates of 48%, 40% and 15% were observed in preloaded, prestripped and surgeon-stripped DMEK grafts, respectively. Rebubbling rates were significantly associated with combined cataract surgery (p=0.009) and with time from harvesting the graft to the surgery (p=0.02).ConclusionsDecreased adhesion forces and elastic modulus in eye bank prepared tissues may contribute to increased rebubbling rates.